Implementation of Solar-Powered Water Pump and Monitoring System for Hydroponic Urban Farming - Marindra, Adi Mahmud Jaya; Santaki, Dwi Surya; Kurniawan, Deny; Maulana, Ferdian Ilham; Widjaksana, Raihan Adji; Amzari, Muhammad Irham; Saputra, Pandu Jati Bayu; Minggus, Chenny Azalia Eka Putri; Fauzan, Rafi (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
Hydroponic farming is gaining popularity in urban areas due to its efficient resource usage and high, clean yields. However, systems like the Nutrient Film Technique (NFT) rely on electric pumps for continuous nutrient circulation, making them vulnerable to extended power outages that can disrupt plant nutrition and lead to crop failure. The purpose of this activity is to address the issue of power outages that impacted the hydroponic gardens of the Women Farmers Group (KWT) Sepinggan Raya, Balikpapan, by implementing a solar-powered water pump and a water quality monitoring system. The program consisted of an initial survey, system development and installation, and training sessions on system operation and maintenance. Results indicate that the implementation of the solar pump and monitoring system improves hydroponic productivity while reducing operational costs previously dependent on the national electricity grid. Additionally, the project empowered the local women's group with renewable energy knowledge and modern farming technologies, promoting sustainable urban agriculture practices.Keywords: application of technologies; hydroponic; renewable energy; urban farming; water quality monitoring Abstrak: Pertanian hidroponik semakin populer di area perkotaan yang memiliki keterbatasan ruang karena efisiensi sumber daya dan hasil panen yang tinggi. Namun, sistem hidroponik seperti Nutrient Film Technique (NFT) sangat bergantung pada pompa listrik untuk sirkulasi air nutrisi secara berkelanjutan. Pemadaman listrik yang berkepanjangan dapat mengganggu suplai nutrisi dan berpotensi menyebabkan kegagalan panen. Kegiatan ini bertujuan untuk mengatasi permasalahan padamnya listrik yang terjadi di kebun hidroponik Kelompok Wanita Tani (KWT) Sepinggan Raya, Balikpapan dengan menerapkan pompa air tenaga surya dan sistem pemantauan kualitas air. Kegiatan meliputi survei awal, pengembangan dan instalasi sistem, serta pelatihan pengoperasian dan pemeliharaan teknologi bagi para petani. Hasil menunjukkan bahwa sistem ini meningkatkan produktivitas kebun hidroponik dan mengurangi ketergantungan terhadap jaringan listrik nasional (PLN). Selain itu, proyek ini memberdayakan kelompok tani dengan pengetahuan tentang energi terbarukan dan teknologi pertanian modern, mendorong praktik pertanian yang berkelanjutan di lingkungan urban.Kata kunci: energi baru terbarukan; hidroponik; monitoring kualitas air; penerapan teknologi; urban farming